MICRO-CLIMATIC PATTERNS OF LAND DEGRADATION/DESERTIFICATION STATUS IN A PART OF NORTH-EASTERN SUDANO-SAHELIAN ZONE OF NIGERIA - Ndabula, C.; Jidauna, G. G.; Oyatayo, K.; Ati, O. F. (FUDMA JOURNAL OF SCIENCES, 2023)
This study aimed at assessing and mapping patterns of Micro-Climatic Sensitivity Areas (MCSA) to depict the spatio-temporal patterns of desertification status This was achieved based on the evaluation and mapping of a micro-climatic sensitivity index (MCSI ) and sensitivity areas (MCSA) respectively. This was derived from three micro-climatic indices Aridity Index (AI), Land Surface Albedo Index (LSA), and Land Surface Temperature Index (LST) using the MEDALUS approach. These indicators mapped using acceptable algorithm on relevant landsat satellite data bands of (1987, 2000, and 2015) and rainfall data for the corresponding years of the satellite images. Spatio-temporal patterns of desertification status (extent, rate and intensity) was determined based on the extents of sensitivity classes using landscape change structural indices; Dynamic Rate of Change (Ki), Change Intensity (Li) indices, while Annual Rate was estimated using logarithmic approach. Results showed that of the 30373 km2 total extent of study area, the distribution of mean extents of various micro-climatic sensitivity areas (MCSAs) as follows; Very High, 4348 km2 (14.32%), High, 6035 km2 (19.87%), Moderate, 8247 km2 (27.15%), Low, 5975 km2 (19.67%) and Very Low, 5770 km2 (18.99%). Annual rate of expansion which were generally observed to be low were as follows; VH, 1.139 km2, H, 0.949 km2 and M, 0.917 km2 and decline; Low, 1.00 km2, VL, 1.16 km2. Intensification of desertification for the whole period were generally very low as follows; VH, 0.01%, H, 0.03% and M, 0.008%, while rejuvenation was also characteristically very slow as follows;